Characterization of RA839, a noncovalent small molecule binder to keap1 and selective activator of Nrf2 signaling - Winkel, Angelika F.; Kannt, Aimo (The journal of biological chemistry, 2015)
The activation of the transcription factor NF-E2-related factor 2 (Nrf2) maintains cellular homeostasis in response to oxidative stress by the regulation of multiple cytoprotective genes. Without stressors, the activity of Nrf2 is inhibited by its interaction with the Keap1 (kelch-like ECH-associated protein 1). Here, we describe (3S)-1-[4-[(2,3,5,6-tetramethylphenyl) sulfonylamino]-1-naphthyl]pyrrolidine-3-carboxylic acid (RA839), a small molecule that binds noncovalently to the Nrf2-interacting kelch domain of Keap1 with a Kd of ∼6 μm, as demonstrated by x-ray co-crystallization and isothermal titration calorimetry. Whole genome DNA arrays showed that at 10 μm RA839 significantly regulated 105 probe sets in bone marrow-derived macrophages. Canonical pathway mapping of these probe sets revealed an activation of pathways linked with Nrf2 signaling. These pathways were also activated after the activation of Nrf2 by the silencing of Keap1 expression. RA839 regulated only two genes in Nrf2 knock-out macrophages. Similar to the activation of Nrf2 by either silencing of Keap1 expression or by the reactive compound 2-cyano-3,12-dioxooleana-1,9-dien-28-oic acid methyl ester (CDDO-Me), RA839 prevented the induction of both inducible nitric-oxide synthase expression and nitric oxide release in response to lipopolysaccharides in macrophages. In mice, RA839 acutely induced Nrf2 target gene expression in liver. RA839 is a selective inhibitor of the Keap1/Nrf2 interaction and a useful tool compound to study the biology of Nrf2.
Gesehen am 24.01.2018